Surgery alone or surgery with a combination radiation or chemoradiation for management of patients with bulky-stage IB2 cervical carcinoma. Issue 3 (1st April 2006) - Micha, J. P.; Goldstein, B. H.; Rettenmaier, M. A.; Brown, J. V.; John, C. R.; Markman, M.
Abstract : The management of stage IB2 cervical carcinoma remains controversial. This retrospective review evaluates 47 IB2 cervical carcinoma patients treated with surgery alone (S), surgery plus postoperative radiotherapy (SR), or surgery plus postoperative chemoradiation (SRC). Median progression-free interval (PFI) was 70.3 months for the SR group ( n = 21), 73.3 months for the SRC group ( n = 15), and 33.5 months for the S group ( n = 11). The survival rate was 76% for the SR group, 87% for the SRC group, and 55% for the S group. Overall 5-year survival rate for the three groups was 75%. Median follow-up for the patient population was 61.3 months. The number of the patient and the nonrandomized nature of this study preclude any definitive conclusions, but interestingly, the SRC and SR groups exhibited a substantially better PFI and overall survival compared to the S group. Selection bias does not appear to be a factor since patients in SR or SRC group were at greater risk for recurrence (eg, higher incidence of deep stromal invasion, parametrial involvement) than patients in the S group; yet, they still experienced superior PFI and overall survival. Further studies comparing postoperative irradiation and chemoradiation with these patients in a randomized phase 3 trial may be warranted.